La Universidad Laica VICENTE ROCAFUERTE de Guayaquil como aliado estratégico del sector empresarial de la zona 8 - Guamán Aguiar, Stalin (2018)
The present study shows an analysis of the viability of the investment to create an Accounting ConsultancyCenter at Universidad Laica VICENTE ROCAFUERTE de Guayaquil. The research advances of the IC-ULVR 16-52 project are presented, which seeks to improve the productive matrix of Ecuador based on advice and training. The current situation of a sample of companies in zone 8 of Ecuador was characterized. Some of the antecedents of this sector are described. The results of applying an inductive investigation to managers of the accounting, tax and administrative areas of companies that carry out their activities in zone 8 are shown. They allowed to determine the high level of acceptance to hire the advisory services in the mentioned areas in addition to training and continuing education. Supply and demand (including unmet demand) of advisory services that exist in the studied area were identified.